CCL2-CCR2 Axis Potentiates NMDA Receptor Signaling to Aggravate Neuropathic Pain Induced by Brachial Plexus Avulsion. (15th January 2020) - Xian, Hang; Jiang, Yi; Zhang, Hang; Ma, Sui-bin; Zhao, Rui; Cong, Rui
Highlights: CCL2-CCR2 is highly expressed in brachial plexus avulsion (BPA) induced neuropathic pain model. CCR2 was mainly expressed on astrocytes and neurons in the spinal cord after BPA injury. Spinal astrocytes-derived CCL2 interacted with CCR2 receptor in neurons to activate NMDA receptor in rats exposed BPA injury. CCR2 could be a potential therapeutic target for BPA induced neuropathic pain. Abstract: Brachial plexus avulsion (BPA) represents the most devastating nerve injury in the upper extremity and is always considered as a sophisticated problem due to its resistance to most standard pain relief medications or neurosurgical interventions. There is also a lack of understanding on the underlying mechanisms. Our study aimed to investigate whether spinal CCL2-CCR2 signaling contributed to the development of neuropathic pain following BPA via modulating glutamate N-methyl-d -aspartate receptor (NMDAR). A rat model of BPA on lower trunk (C8-T1) was established, and the sham- and BPA-operated animals were intrathecally injected with saline, C-C chemokine receptor type 2 (CCR2) inhibitor INCB3344 and NMDAR antagonist DL-AP5 one week postoperatively, the behavioral performance of the treated animals and expressions of C-C motif ligand 2 (CCL2), CCR2, and N-methyl-D-aspartic acid receptor 2B (NR2B) in spinal cord sections of each group were examined. It was shown that BPA injury significantly reduced mechanic withdrawal thresholds the next day after surgery until the end of the observation. Both CCL2 and CCR2 expressions increased in BPA rats compared to those in sham rats. CCL2 was mainly localized in astrocytes, and CCR2 was preferably expressed on astrocytes and neurons. Besides, NMDAR subunit NR2B increased in BPA-operated rats, which was reversed in response to CCR2 and NR2B inhibition. However, these inhibitors didn't change the spinal NMDAR level in sham rats. CCR2 and NMDAR inhibition efficiently alleviated mechanical allodynia caused by BPA either at early or late phase of neuropathic pain. Collectively, CCL2-CCR2 axis is associated with mechanical pain after BPA by elevating NMDAR signaling.